The marshal's baton: There is no bomb, there was no bomb, they were not looking for a bomb - Svend Aage Christensen (Danish Institute for International Studies (DIIS), 2009)
In a letter dated 6 January 2009, the Danish foreign minister, Per Stig Møller, asked DIIS to draw up a report based on the documentary evidence concerning the 1968 crash of a B-52 bomber on the sea ice a few miles from Thule Air Base in Northwestern Greenland. The B-52 had four hydrogen bombs on board. For more than four decades, the official American and Danish explanations have consistently stated that all four nuclear weapons were destroyed in the accident. The foreign minister's initiative was caused by a debate in the Parliament (Folketing) over some programmes and articles carried by the BBC on November 10 and 11, 2008. When DIIS received the Foreign Minister's request for an investigation into the Thule accident, the Director asked senior researcher Svend Aage Christensen, coordinator of a major research effort in 1996-97 on 'Greenland During the Cold War: Danish and American Security Policy 1945-68' to investigate the matter. The result of the investigation is presented in this report.
Keywords: 300